Eco-friendly mixed metal (Mg–Ni) ferrite nanosheets for efficient electrocatalytic water splitting - Malima, Nyemaga M.; Khan, Malik Dilshad; Masikane, Siphamandla C.; de Souza, Felipe M.; Choi, Jonghyun; Gupta, Ram K.; Revaprasadu, Neerish (Scientific reports, 2023)
Eco-friendly and cost-effective catalysts with multiple active sites, large surface area, high stability and catalytic activity are highly desired for efficient water splitting as a sustainable green energy source. Within this line, a facile synthetic approach based on solventless thermolysis was employed for the simple and tunable synthesis of Ni 1−x Mg x Fe 2 O 4 (0 ≤ x ≤ 1) nanosheets. The characterization of nanosheets (via p-XRD, EDX, SEM, TEM, HRTEM, and SAED) revealed that the pristine ferrites (NiFe 2 O 4 and MgFe 2 O 4 ), and their solid solutions maintain the same cubic symmetry throughout the composition regulation. Elucidation of the electrochemical performance of the nanoferrite solid solutions showed that by tuning the local chemical environment of Ni in NiFe 2 O 4 via Mg substitution, the intrinsic catalytic activity was enhanced. Evidently, the optimized Ni 0.4 Mg 0.6 Fe 2 O 4 catalyst showed drastically enhanced HER activity with a much lower overpotential of 121 mV compared to the pristine NiFe 2 O 4 catalyst. Moreover, Ni 0.2 Mg 0.8 Fe 2 O 4 catalyst exhibited the best OER performance with a low overpotential of 284 mV at 10 mA/cm 2 in 1 M KOH. This enhanced electrocatalytic activity could be due to improved electronic conductivity caused by the partial substitution of Ni 2+ by Mg 2+ in the NiFe 2 O 4 matrix as well as the synergistic effect in the Mg-substituted NiFe 2 O 4 . Our results suggest a feasible route for developing earth-abundant metal oxide-based electrocatalysts for future water electrolysis applications.